PERTANGGUNGJAWABAN YURIDIS DALAM TRANSAKSI LAYANAN MEDIS (TRANSAKSI TERAPEUTIK) TERMASUK INFORMED CONSENT ATAS TINDAKAN MEDIS PADA RUMAH SAKIT - Mahadian Tri Ekasari (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2020)
This research resulted, First, with the informed consent not necessarily the medical staff / doctor cannot be sued or prosecuted, precisely with the existence of this informed consent the medical staff / doctor must work professionally and in accordance with operational standards as stated in informed consent. Second, hospitals as legal entities (corporations) can be prosecuted and accounted for by malpractice actions of health workers in hospitals. Article 46 of Law Number 44 Year 2009 concerning Hospitals that hospitals must be responsible for negligence committed by doctors practicing in hospitals is a burden borne by the owner and management of the hospital. Third, there are several efforts that can be taken in the event of negligence or malpractice by health workers / doctors / hospitals, namely by reporting to the MKEK / MKDKI, conducting mediation, civil litigation and criminal reporting.Keywords: Informed Consent, Patient, Hospital